Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 95. Beitrag (Coleoptera: Staphylinidae II, Subfamilie Steninae). - Puthz, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1980)
The Stenines (Coleoptera, Staphylinidae) collected by expedition to Albania made in 1961 by the Deutsches Entomologisches Institut are rcorded and critically examined together with all finds known to the author from publications and various other collections. The material known from Albania totals more than 280 individuals of 38 species, 5 of which are new in Albania (Stenus asphaltinus Erichson, S. intermedius Rey, S. picipes monachus Bernhauer, Stenus coarcticollis drepanensis ssp. nov., S. glacialis Heer). The distribution of the species extant in Albania and the neighbouring countries is listed, including four species new in Bulgaria and one new in Greece. A new species from Greece is described (Stenus parnassianus spec. nov.). With regard to zoogeography, a little more than half of the Albanian Steninae belong to the Submediterranean or Mediterranean fauna, while the other species represent Euro-Sibirian elements.Nomenclatural Actsparnassianus Puthz, 1980 (Stenus (Stenus)), spec. n.drepanensis Puthz, 1980 (Stenus coarcticollis), sspec. n.